Pre-inoculation of ago2 and DCL2/4-deficient Nicotiana benthamiana plants with the Pepino mosaic virus EU mild isolate confers complete protection against superinfection with the aggressive isolate - Spanos, Theodore; Ghodbane, Amira; Rezazga, Aya; Ludman, Márta; Fátyol, Károly; Elbeaino, Toufic; Livieratos, Ioannis (Frontiers in Virology, 2025)
The phenomenon whereby plants infected with a mild isolate of a virus are cross-protected from subsequent “challenge” inoculation with a severe isolate of the same virus resembles mammalian vaccination and was first described almost 100 years ago. In this study, the ability of wild type (wt), ago2- and DCL2/4-deficient Nicotiana benthamiana plants “vaccinated” with the mild (Sp13) PepMV isolate to exert a cross-protective response against “challenge”-inoculation with a severe (PCH, aggressive) isolate was investigated. Initially in wt and ago2-deficient plants, two interval-times (5 and 10 days) between inoculations were used and virus accumulation was analyzed in newly-formed (systemic) leaves. In follow up experiments, wt and DCL2/4-deficient plants were inoculated using a single interval-time (5 days) and both inoculated (local) and systemic leaves were analyzed. In both experiments, leaves were collected 3 days post “challenge”-inoculation and immunoblot, northern blot and RT-qPCR assays demonstrated the complete blockage of the PCH aggressive isolate, which remained at undetectable levels. Using a similar experimental set-up with wt and ago2-deficient N. benthamiana plants and the genetically distinct Potato virus X as the “challenge”-inoculum, complete blockage of superinfection was not observed but instead a significant reduction of PVX RNA levels systemically. Collectively, our results cannot entirely exclude the complete redundancy of two essential components of RNA silencing, but clearly suggest the activation of an efficient and durable superinfection protection mechanism, which is distinct to it.